Dynamic of coral recruits in the Karimunjawa National Park, Central Java, Indonesia - SUKMARAHARJA AULIA RACHMAN TARIGAN; MUNASIK MUNASIK; DIAH PERMATA WIJAYANTI; MUHIDIN MUHIDIN; ENDANG ABDUL ROHMAN; SHINTA PARDEDE (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Tarigan SAR, Munasik, Wijayanti DP, Muhidin, Rohman EA, Pardede S. 2024. Dynamic of coral recruits in the Karimunjawa National Park, Central Java, Indonesia. Biodiversitas 25: 869-880. After a disturbance event, coral reefs can recover naturally by recruiting new corals. These can be affected by environmental factors like the substrate's physical and biological structure, predation, and accidental mortality of recruits by grazers, as well as the number and size of parent corals supplying larvae. This study examined the connection between newly recruited corals and biological factors such as sea urchin density, herbivorous fish abundance, and hard coral coverage. The study was monitored changes in coral cover, juvenile coral density, herbivore abundance, and hard coral coverage at 43 locations and two depths (shallow; 2-3 m) and deep (8-10 m) from 2013 to 2022. The locations were distributed across six different zone systems: the core zone, protection zone, tourism zone, traditional fisheries zone, aquaculture zone, and rehabilitation zone. Multiple Linae Regression, ANOVA test, and Principal Component Analysis were employed to assess the relationship between coral recruitment and other variables. Results indicated that the coral recruitment density was not significantly different when comparing different zoning systems (two-way ANOVA test, P-value>0.05). Based on the PCA analysis, we found that in 2013 and 2019, excavator, sea urchin, browser, and hard coral have a positive relationship with coral recruitment, which implies that coral recruitment would increase as sea urchin, browser, and hard coral increase. Meanwhile, in 2019 and 2022, coral recruitment has a negative relationship with scraper, and also with hard coral growth (although only in 2022), implying that coral recruitment would decrease if scraper and hard coral increase. The study recommends restoring the role of herbivorous species in Karimunjawa National Park (KNP) by prioritizing them in conservation efforts and managing their populations.